Income distribution and the Great Depression - Belabed, Christian A. (Düsseldorf, 2015)
"Recession to the worst economic crisis of capitalism, the Great Depression. However, the role of rising income inequality, which has risen dramatically before both crises, is rarely discussed. In this paper we discuss the rise of top-end inequality and its effects on household consumption, saving, and debt for the 1920s by applying a non-standard theory of consumption, the relative income hypothesis, to the period of interest. We argue that income inequality is linked to the increase of household consumption and the simultaneous decline of household savings as well as rapidly increasing household debt. Thus, the rise of top-end inequality in connection with a broader institutional change, such as the deregulation of financial markets, has contributed to a build-up of financial and macroeconomic instability, in the period leading to the Great Depression."